Number of primordial follicles in juvenile ringed seals (Pusa hispida) from the Gulf of Bothnia and West Greenland - Schmidt, Britta; Hollenbach, Julia; Mühlfeld, Christian; Pfarrer, Christiane; Persson, Sara; Kesselring, Tina; Sonne, Christian; Rigét, Frank; Dietz, Rune; Siebert, Ursula (Animals, 2022)
Primordial follicles are important for the reproduction cycle and, therefore, also for the survival of the whole population of a species. Mammals have a large pool of primordial follicles, and it is thought that this pool represents the total number of oocytes. The aim of the present study was to determine the total primordial follicle number of juvenile ringed seals (Pusa hispida) from the Gulf of Bothnia and Greenland. Overall, 52 ovaries from two ringed seal populations (West Greenland (N = 6), Gulf of Bothnia, region in the Baltic Sea (N = 46)) were examined. All ovaries were cut into 2 mm thick slices and every slice was embedded in paraffin. Out of each tissue block, a 5 µm thick section was cut and stained with haematoxylin-eosin. The mean volume of the follicles and the total volume of primordial follicles per ovary were estimated by stereology and used to calculate the total estimated number of primordial follicles. The median of the total estimated number of primordial follicles seemed to be higher in Baltic individuals than in Greenland individuals (Gulf of Bothnia = 565,657; Greenland Sea = 122,475). This widens the total range of primordial follicles in ringed seals overall and might bear some potential for discussions regarding the influence of endocrine disruptors and environmental influences depending on different regions/populations and their exposure to various factors. Thus, this study aims to provide basic reference data of the number and mean volume of ringed seal primordial follicles.